The History of Rapa’i Dabôh in Aceh - Anwar Daud; Fauzi Ismail; Abdul Manan; Saprijal Saprijal (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Rapa’i dabôh is a traditional art played by 12 people accompanied with risky attractions using sharp objects namely knife, sword, chainsaw, chain, sharpened bamboo and many else. The aim of this study is to find out the history of rapa’i dabôh in Aceh. The instruments used in this research are observation, interview and documentation. Techniques of data analysis are data reduction, data display and data verification/conclusion. The study revealed that the history of rapa’i dabôh in Aceh was from a prominent ulama named Syekh Abdul Qadir Jailani inherited by Syekh Rafa’i, popularly recognised later as Tarekat Rifa’iyyah. Rapa’i dabôh was early formerly used as media for preaching the Islamic teaching, but later it developed into an art fancied by most the Acehnese people. The spread of rapa’i dabôh was carried by the preachers from north-eastern to southwest-southern part of Aceh, then it inspired many groups of performance such as Rincong Pusaka at Ie Lhop village, Tangan-Tangan, Southwest Aceh and Putra Naga at Mutiara village, Sawang, South Aceh. Both groups still exist until today.